Penerapan Larangan Magrib sebagai Solusi Mengatasi Agency Problem dalam Akad Mudharabah - Ali Wardani; Wahyuddin Abdullah; Rika Dwi Ayu Parmitasasri (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, Indonesia, 2024)
The mudharabah (profit sharing) agreement is a contract that is characteristic of sharia financial institutions. However, agency problems often occur in mudharabah contracts. This article discusses the prevention of mudharabah contract agency problems through the prohibition of maghrib (maisir, gharar, usury and falsehood). The aim is to provide alternative solutions in overcoming mudharabah contract agency problems. The research method used is qualitative literature with a descriptive approach. Primary and secondary data collected through orientation and exploration will be analyzed using inductive and deductive techniques. The results explain that potential agency problems can be reduced by implementing sunset prohibitions (maisir, gharar, usury and falsehood) in the mudharabah contract evaluation process. Both in management processes and financial reports, sunset analysis can be applied to detect or avoid information asymmetries.